Surface‐Selective Grafting of Crosslinking Layers on Hydrogel Surfaces via Two Different Mechanisms of Photopolymerization for Site‐Controllable Release. Issue 20 (28th May 2018) - Zhang, Jiaojiao; Nie, Jun; Zhu, Xiaoqun
Abstract: This study reports an effective method for controlling substance‐release sites of hydrogel. Glycidyl methacrylate, which contains two functional groups, namely, double‐bond acrylate and epoxide, is photografted on a hydrogel surface through hydrogen abstraction photopolymerization due to the existence of a hydrogen donor, such as an amine, in the hydrogel matrix. The remaining epoxide group crosslinks the polymer chain of polyglycidyl methacrylate. Substance release of hydrogel is changed due to the altered surface texture of hydrogel. Rate and site‐controlled substance release are achieved by controlling the thickness and site of surface grafting and the extent of epoxide ring opening. This study may provide a novel method for achieving hydrogel function or modified performance of other biomaterials to meet biological activity requirements. Abstract : A method to surface‐selectively graft a crosslinking layer on the surface of hydrogel through radical and cationic photopolymerization is reported. Rate and site‐controlled substance release of hydrogel are achieved by controlling the thickness and site of surface grafting and the extent of epoxide ring opening.